A critical analysis of the adequacy of data protection law in Bangladesh: Challenges and potential solutions / Md. Toriqul Islam - Md. Toriqul , Islam (2021)
Privacy is essential for the fullest expression of the physical and mental development of humankind. It has become one of the most desired human rights and basic needs for human life in this era of ubiquitous computing. In this digital age, diverse activities are going on online using personal data, and these lead personal data to evolve as the new fuel to the Internet, and coin to the digital world. The discovery of the Internet, the World Wide Web, constant progress in information and communication technologies, the Internet of Things and similar other technologies or devices have facilitated the collection, processing and storing of personal data to an unprecedented level. Over time, governments, businesses, and other entities have been processing large scale of personal data for numerous purposes, mostly, without the knowledge of the persons concerned. Therefore, information privacy gains the momentum than any other aspect of privacy. This landscape poses tremendous challenges to information privacy as well. Consequently, information privacy appears as one of the hot button issues in contemporary global politics, policies, and business. In response, the protection of privacy, especially, data privacy has been recognised nationally, regionally, and internationally, as evidenced by numerous initiatives of all these entities. To date, nearly one hundred and fifty countries have enacted either sectoral, or comprehensive data protection laws, and many other nations have started the process of enacting such laws to ensure the rights of the data subjects. Like other nations and regions, the people of Bangladesh are also experiencing various privacy threats, and accordingly, deserve to have adequate legal protections. Nonetheless, there is no comprehensive data protection law to date and even academic research in the context of Bangladesh. This backdrop requires extensive research as to whether the existing legal regime of Bangladesh ensures adequate legal protections for privacy in comparison with international and regional data protection standards. Using doctrinal legal research, or desk-based or library research methods, this research aims to fill that gap. The findings of this study reveal that though there is no comprehensive data privacy law in Bangladesh, citizensï¿½ right to privacy is conditionally recognised in the Constitution, and there are references and recognition of some aspects of privacy in numerous existing laws, and case laws. Hence, the results demonstrate that the existing legal regime of Bangladesh does not provide adequate legal protections for the right to privacy and personal data of the individuals, and thus, require significant policy drives. Against such backdrops, this thesis offers some policy recommendations for all stakeholders, and especially, recommends the policymakers for enacting a comprehensive data protection law in Bangladesh. Notably, this thesis introduces a model for a suitable data protection law of Bangladesh based on the international and regional data protection standards, best practices, and especially, in conformity with the General Data Protection Regulation of Europe. The findings of this research will enlighten the relevant stakeholders to understand the issues encompassing privacy and personal data protection in Bangladesh and facilitate them to map and design their future strategies and policy directions.